Voltage-mode low-pass, high-pass, band-pass biquad filter using simple CMOS OTAs - Kumngern, Montree; Dejhan, Kobchai (My University, 2009)
A high input impedance electronically tunable voltagemode biquadratic filter with single input and three outputs using four simple CMOS operational transconductance amplifiers and two grounded capacitors is proposed. The proposed filter provides low-pass, band-pass and high-pass voltage responses at a high input impedance terminal, which enables easy cascadability of the voltage circuit. Also, the parameters ωo and Q can be set orthogonally by adjusting the circuit components. For the realizing of all the filter responses, no critical matching condition is required, on inverting-type input signal is imposed and all the incremental parameter sensitivities are low. The performances of the proposed circuit are simulated with PSPICE to confirm the presented theory. The band-stop and all-pass responses can also be obtained by interconnection of relevant output voltages with summer circuits. © 2009 IEEE.
Keywords: Biquad filter; Electronically tunable; Ota; Voltage-mode